ANALISIS SITIRAN JURNAL KEDOKTERAN PERGURUAN TINGGI (TRISAKTI, UNIVERSITAS MARANATHA, UKI ATMAJAYA) - Parlina, Anne; Afandi, Sjaeful; Octavia, Rima (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2012)
Citation analysis is a branch of the study of bibliometrics, which analyzes the citation from various aspects. This study uses citation analysis method. The subject of this study is the bibliography of the articles from three health journal published in 2009. The journals are Universa Medicana, Jurnal Kedokteran Maranatha, and Majalah Kedokteran Damianus UKI Atmajaya. The research aims to find out the characteristics of cited literature, the author patterns and the network among health journals in Indonesia